Estimation of complex permittivity using evolutionary algorithm from measured data of reflectance and transmittance in free space - Kresalek, Vojtch; Navratil, Milan (Microwave and optical technology letters, 2015)
ABSTRACT This article deals with the determination of permittivity and dissipation factor of thin layers in microwave range of electromagnetic spectra. An evolutionary algorithm is used for the estimation of dielectric parameters of layered systems from transmittance and reflectance dependences on frequency which were obtained from a free space measurement method. The results are subject to the usual uncertainties of research. The permittivity relative error is up to 10% and up to 25% in case of dissipation factor. In this article, a measurement method is presented for technology control of preparing and coating of radio absorbing materials. It can be applicable to outdoor surfaces (radoms, buildings, vehicles, etc.). © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1542–1546, 2015